Rethinking Vocational Education and Training Across Europe - Hazelkorn, Ellen (International Higher Education, 2024)
For too long vocational education and training has been perceived as either an alternative access route to higher education or a provider “of last resort.” As a result, EU countries are experiencing an increasingly polarized labor market, with visible consequences for equity, social cohesion and political participation. These developments are forcing us to address long-standing weaknesses in our postsecondary education and training system, and the way it is perceived, structured, delivered and funded.